Work Discipline on Employee Performance Through Work Productivity - Tasya, Cut Yeni; Akbar, Mohammad Aldrin; Lina, Ros (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study examines the effect of work productivity on employee performance at PT Paguntaka Cahaya Nusantara Papua and West Papua Branch. Research Design and Methodology: Data was collected using a cross-sectional research design through a survey involving employees from various departments. Regression analysis evaluated the relationship between work productivity and employee performance. Findings and Discussion: The results showed a positive and significant relationship between work productivity and employee performance, with a regression coefficient of 0.62 and a p-value of 0.0001. This finding supports theories that link work productivity with performance improvement and confirms the importance of productivity factors in achieving optimal organizational performance. Implications: This study makes a significant contribution to scientific and managerial practice by providing empirical evidence and recommendations for managers to develop policies that encourage work productivity. However, its limitations include its cross-sectional design and limited generalizability. Future research should use a longitudinal design and expand the sample to various industries to gain more insight into the relationship between work productivity and employee performance.